High-resolution spherical directivity of live speech from a multiple-capture transfer function method - Leishman, Timothy W.; Bellows, Samuel D.; Pincock, Claire M.; Whiting, Jennifer K. (The Journal of the Acoustical Society of America, 2021)
Although human speech radiation has been a subject of considerable interest for decades, researchers have not previously measured its directivity over a complete sphere with high spatial and spectral resolution using live phonetically balanced passages. The research reported in this paper addresses this deficiency by employing a multiple-capture transfer function technique and spherical harmonic expansions. The work involved eight subjects and 2522 unique sampling positions over a 1.22 or 1.83 m sphere with 5° polar and azimuthal-angle increments. The paper explains the methods and directs readers to archived results for further exploration, modeling, and speech simulation in acoustical environments. Comparisons of the results to those of a KEMAR head-and-torso simulator, lower-resolution single-capture measurements, other authors' work, and basic symmetry expectations all substantiate their validity. The completeness and high resolution of the measurements offer insights into spherical speech directivity patterns that will aid researchers in the speech sciences, architectural acoustics, audio, and communications.